DETERMINATION OF THE GEOMETRIC AND KINEMATIC PARAMETERS OF THE DEVELOPED CHAIN GEAR FOR THE 2SB-10 DRYER - YULDASHEV, KHURSHID (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article presents the calculated data for determining the geometric and kinematic parameters of the developed chain transmission for the 2SB-10 cotton dryer. The chain transmission scheme and the chain pitch are selected, according to which other parameters of the chain transmission are determined.